Osteoporosis as a result of the long-term administration of glucocorticoids in patients suffering from acantholytic pemphigus - M. A. Ufimtseva; YU. M. Bochkarev; E. P. Gurkovskaya; P. S. Puhtinskaya; K. I. Nikolaeva; O. D. Lesnaya (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
Goal. To study the prevalence of glucocorticoid-induced osteoporosis in patients suffering from acantholytic pemphigus and risk of osteoporosis-related fractures. Materials and methods. The study involved 26 patients including 12 patients suffering from acantholytic pemphigus. The patients underwent dual-energy X-ray absorptiometry (DXA) for calculating bone mineral density (BMD) as well as T and Z scores. To assess the ten-year probability (absolute risk) of fractures, the FRAX model was applied. Major results. Glucocorticoid-induced osteoporosis was diagnosed in 33.3% of the AP patients receiving a glucocorticoid therapy, and osteopenia was also diagnosed in 33.3% of them; an increased risk of osteoporosis-related fractures was observed in all of the patients over 40, which entails the need in early diagnostics of pathologic bone changes and prevention of complications such as osteoporosis-related fractures. Conclusion. A high share of complications (83.3%) related to systemic GCS stipulates the need in increased cooperation between dermatologists and allied specialists.